Caracterização de células-tronco mesenquimais isoladas do líquido amniótico humano e submetidas ao processo de criopreservação. - Patricia Caroline Angelo (2010)
Introduction: in the cell therapy context, cryopreservation of mesenchymal stem cells from human amniotic fluid has a great clinical importance since these cells can be harvested even in the prenatal period and can be stored for use in future treatments. Objectives: This study aimed to characterize the mesenchymal stem cells cultured from human amniotic fluid before and after the cryopreservation process, as to maintain their multipotent differentiation capacity, viability andchromosomal stability. Methodology: The study included samples from pregnant women, which were grown, characterized and subjected tocryopreservation for 150 days. For the cellular characterization, flow cytometry tests were performed to determine the immunophenotypic profile of cultured cells, cell differentiation, karyotype determination and cell viability. To check the maintenance of cell characteristics after cryopreservation, the cells were thawed and then tests of cell viability, culture, cell differentiation and karyotype were performed again. In order to verify the interference of cryopreservation on the gene expression associated with pluripotency, octamer 4 (OCT-4) this gene expression was quantified before and after cryopreservation. Results: These cellscharacterization showed that those cells grown from human amniotic fluid present morphology and immunophenotypic profile characteristic of mesenchymal stem cells and also have the ability to differentiate into cells of mesodermal lineage. The study also showed that from criobiology techniques, these cells can be cryopreserved for at least five months and be recovered after this period, maintaining its ability to in vitro growth and differentiation and still maintaining OCT-4 gene expression, thereby indicating the maintenance of its characteristic of stem cell. Moreover, these cells karyotype analysis indicated that both culture andcryopreservation did not induce the appearance of chromosomal aberrations, which is important for a possible therapeutic use. Conclusion: This study concluded that the cryopreservation technique of cells from amniotic fluid can be an extremely useful tool in maintaining the capacity of multipotent stem cells collected during pregnancy.